Knowledge and Attitude Regarding Hepatitis-B Prevention among People of Lahore Community, Pakistan - Khan, Asaf; Ali, Muhammad; Rafiullah, . (International Journal of Social Sciences and Management, 2017)
Hepatitis-B is a communicable disease and globally a public health problem with a complicated pathology of liver, which disturbs the normal function of the liver caused by Hepatitis-B virus known as HBV. This study aims to determine knowledge and attitude regarding Hepatitis-B prevention among people of Lahore community, Pakistan. Cross-sectional survey technique was used in current study. The self-administered questionnaire distributed to the 200 participants through convenient random sampling. Descriptive analysis was used to analyze the data using SPSS (statistical package for social science studies) version 21.The findings of the current study showed, poor knowledge and negative attitude of the participants toward prevention and treatment of Hepatitis-B in the community of Lahore, Pakistan. Moreover they were preferred home remedies, complementary therapies and spiritual healers as compared to medical treatment. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 68-76